(untitled) (Acta Scientiarum. Animal Sciences, 2026)
This study aimed to evaluate the effects of Moringa oleifera leaf meal and its aqueous extract on the semen quality of Nigerian Indigenous Normal Feathered Cocks (NINFC). A total of 375 birds were divided into five treatments, each receiving different levels of Moringa oleifera supplementation in their diets and extenders. Semen quality parameters such as sperm concentration, motility, viability, and lipid peroxidation were assessed. The results showed that Moringa oleifera supplementation improved sperm motility and viability, with the 15% inclusion level yielding the highest sperm viability and motility during cold storage (5â„ƒ). Additionally, the antioxidant properties of Moringa significantly reduced lipid peroxidation, especially at the 10% and 25% inclusion levels. The findings suggest that Moringa oleifera leaf meal, due to its rich nutritional composition and antioxidant benefits, holds promise as a dietary supplement for enhancing reproductive efficiency and semen preservation in indigenous poultry breeds. This has implications for improving the productivity of indigenous chickens in developing regions.